Development video media using study strategies groups for facial skin care learning not problems beauty cosmetology SMK Negeri 3 Pematang Siantar - Fauzani, Asrah Rezki; Ampera, Dina (Jurnal Pendidikan Teknologi Kejuruan, 2023)
Education in Indonesia is constantly evolving. This condition presents a challenge for learning, particularly in the realm of educationwhich functions to provide certain knowledge, insights, skills and expertise. To introduce an innovative teaching paradigm, it is necessary to develop teaching methods and media. In order to achieve innovative teaching goals, educators must have instructional media as a supporting tool or method for conveying material, so as to motivate students and enhance their learning. One of the media that can support the learning process by using visual media as an interactive learning medium is learning videos. The purpose of this learning is to develop and test the feasibility of a valid instructional media video on the No Problem Facial Skin Care competency. The objects of this research inlcude material experts, media experts and students of SMK Negeri 3 Pematang Siantar. The research method is developed by utilizing the R&D (Research & Development). Data collection was carried out using a questionnaire. The research results for the material expert validity test yielded a score of 92.53 percent, while media experts scored 89 percent, and it was determined that the use of interactive video learning media improved student learning outcomes. According to experts, learning video media is ideally suited for use as learning media competencies in No Problem Facial Skin Care.